2020
DOI: 10.1136/bmjopen-2018-026876
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and fracture risk: a systematic review and exploratory meta-analysis of observational studies

Abstract: ObjectivesThis review provides insights into the potential for aspirin to preserve bone mineral density (BMD) and reduce fracture risk, building knowledge of the risk-benefit profile of aspirin.MethodsWe conducted a systematic review and exploratory meta-analysis of observational studies. Electronic searches of MEDLINE and Embase, and a manual search of bibliographies was undertaken for studies published to 28 March 2018. Studies were included if: participants were men or women aged ≥18 years; the exposure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…In a review examining the association between aspirin use and fracture risk, the authors included a table presenting for each included study the citation, study design, country, sample size, setting, mean age, percentage of females, number of years follow-up, exposure details, and outcomes assessed (table 2). 191…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In a review examining the association between aspirin use and fracture risk, the authors included a table presenting for each included study the citation, study design, country, sample size, setting, mean age, percentage of females, number of years follow-up, exposure details, and outcomes assessed (table 2). 191…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In addition to its antiplatelet activity, aspirin may also affect oxidative stress, vascular in ammation, and insulin sensitivity [18][19][20][21][22][23]. Recent studies have shown that low-dose aspirin can affect bone metabolism[13, [24][25][26][27][28][29][30]. But these research results are contradictory and controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Allied health services (eg, physiotherapy) play a key role in early mobilization and functional recovery after MOF in many countries, ( 24,25 ) and non‐opioid analgesics are widely known to be efficient in reducing pain—pain being a dimension of the EQ‐5D‐3L utility score used to calculate HRQoL in this study. ( 26 )…”
Section: Discussionmentioning
confidence: 99%